The Effect of Bug-in-Ear eCoaching on Pre-Service Teachers’ Implementation of Functional Communication Training - Melih Çattık; Esra Orum-Çattık; Ahmet İlkhan Yetkin (Behavioral Sciences, 2025)
The study examined the effect of BIE eCoaching on the functional communication training (FCT) implementation skills of pre-service teachers (PTs) and the effect of FCT implemented by PTs on reducing problem behaviors and increasing communication skills of children with autism spectrum disorder (ASD). After the intervention, it was examined whether PTs and children with ASD maintained and generalized the acquired behaviors. Moreover, PTs answered a social validity form before and after the intervention. The methodology of this study involved single-subject research with a multiple-probe design between pairs of participants. The BIE eCoaching intervention was effective in children with ASD’s use, maintenance, and generalization of FCT. FCT was effective in reducing problem behaviors, increasing communication skills, and maintaining and generalizing these skills in children with ASD. Social validity findings showed that PTs’ perceptions of BIE eCoaching changed positively at the end of the intervention.